Impacts of environmental conditions and management of sluice gates on glass eel migration. (5th December 2022) - Bouchard, Colin; Boutron, Olivier; Lambremon, Jordane; Drouineau, Hilaire; Lambert, Patrick; Nicolas, Delphine
Abstract: Anthropogenic barriers such as tidal gates impair animal migration and ecological continuity. For migratory fishes, barriers may alter or impeach both upstream and downstream migrations. Juveniles of European eels, namely glass eels, have to pass those barriers when migrating upstream, whereas they have limited swimming capacities and are dependent on several environmental variables. Hydrological conditions, which can be modified by barrier management, are critical for glass eels. Here, we investigated the links between hydrological conditions and barrier management and the recruitment of glass eels at a connection between the Mediterranean Sea and a lagoon. To do that, we modeled the recruitment of glass eels over ten seasons accounting for temporal variations and co-variable effects. We modeled three aspects of recruitment: presence, level, and composition. We found that monthly and inter-annual effects explained the main part of the variations in glass eel recruitment but accounting for environmental effects improved our models, with a positive effect of temperature, for instance. We associated low levels of catches and recruitment of rather old individuals to high water flow rates when water flows out of the lagoon. Those results call for further studies on how sluice gate management may improve glass eel recruitment and seem to indicate that local stakeholders should adjust the number of open gates depending on the water level on both sides of the barrier. Highlights: We found inter & intra-seasonal variations in glass eel a French lagoon recruitment. Such temporal variations were also found in pigmentary stages. Outgoing flows (from lagoons to sea) diminish glass eel recruitment. The number of opened gates did not impact the observed recruitment. Local stakeholders should prioritize opening of tide gates at specific water levels.